Antena Planar UWB dengan Pencatuan Tapered-CPW dan Spline-Curved Ground Plane - Agus Dwi Prasetyo; Edwar Edwar (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
The use of radio spectrum in L-to-X bands is currently very diverse, with various types of devices. Therefore, an antenna with good response on very wide spectrum is expected to be a solution for diverse devices. By widening the antenna bandwidth that is applied to the ultra-wideband (UWB) communication, it is expected to be able to meet wireless communication needs on other bands or frequencies. The UWB antenna has the fractional bandwidth of at least 20% of its center frequency. This paper proposes an attempt to widen the bandwidth of planar UWB antenna with a circular patch (resonator) using coplanar waveguide (CPW). The study was conducted by the phased modification scenario using tapered line and spline-curved ground plane method. This method achieved a UWB antenna with fractional bandwidth of 145.57% (with a testing limit up to 12 GHz frequency) in the size of 40×50 mm2. At the testing bandwidth (L-X band), the basic form antenna (Model A) has a total bandwidth achievement of 39.36% (triple-band); the first antenna modification using tapered line at the feed line (Model B) has total bandwidth achievement of 83.09% (dual-band); and the last antenna modification using the tapered line (from the first modification) with the spline-curved ground plane addition (Model C) has total bandwidth achievement of 91.91% (single-band).